Development and characterization of polyspecific anti-mitochondrion antibodies for proteomics studies on in toto tissue homogenates. - Loro, E; Gianazza, E; Cazzola, S; Malena, A; Wait, R; Begum, S; Brizio, C; Dabbeni-Sala, F; Vergani, L (2009)
We describe the characterization of polyclonal antibodies directed against the whole mitochondrial subproteome, as obtained by hyperimmunization of rabbits with an organelle fraction purified from human skeletal muscle and lysed by sonication. After 2-DE separations with either blue native electrophoresis or IPG as first dimension and blotting, the polyspecific antibodies detect 113 proteins in human muscle mitochondria, representative of all major biochemical pathways and oxidative phosphorylation (OXPHOS) complexes, and cross-react with 28 proteins in rat heart mitochondria. Using as sample cryosections of human muscle biopsies lysed in urea/thiourea/CHAPS, the mitochondrial subproteome can be detected against the background of contractile proteins. When comparing with controls samples from mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes patients, immunoblotting shows in the latter a drastic reduction for the subunits of OXPHOS complex I as well as an increase of several enzymes, including ATP synthase. This finding is the first evidence at the proteomic level of massive up-regulation in a number of metabolic pathways by which the affected tissues try to compensate for the deficit in the OXPHOS machinery.